KEMAMPUAN FISIK ASPEK KESEIMBANGAN DAN KOORDINASI MATA TANGAN PADA ANAK TUNAGRAHITA DI SLB-C YPPLB MAKASSAR - Irvan Irvan; Ilham Kamaruddin; Fachrul Fachrul (UNIVERSITAS NEGERI MAKASSSAR, 2022)
Balance and coordination are elements of physical fitness for anyone, especially children with special needs. This study aims to describe the level of balance and eye-hand coordination in tunagrahita children at SLB-C YPPLB Makassar. This research is a quantitative descriptive study. The instrument in this study used the test method. Standing stork test to measure balance and tennis ball throw and catch test to measure eye-hand coordination. The data analysis technique used descriptive quantitative with percentages. Based on the results of the study, it is known that the balance ability of mentally retarded children in SLB-C YPPLB Makassar mostly has a medium category with a percentage of 40%. While the results of the study showed that the ability of eye-hand coordination in mentally retarded children in SLB-C YPPLB Makassar mostly had a very poor category with a percentage of 40%.